Introduction to Wayang through the Design of the Pandawa Lima Characters in the Metabharata Game - Nur Churul 'Ain Mahmudah; Asidigisianti Surya Patria; Nova Kristiana (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
Abstract The declining interest of young generations in wayang art highlights the need for new media capable of bridging traditional cultural values with contemporary visual trends. This study aims to redesign the Pandawa Lima characters in the Metabharata game using a semi-cartoon–semi-realist visual approach as a medium for introducing wayang culture to young audiences. The research employs a descriptive qualitative method with visual design stages that include reference collection, sketching, coloring, digital rendering, and revisions based on feedback from cultural experts and teenage audiences. Primary data were obtained through semi-structured interviews with two audience groups general teenagers and design students while secondary data were derived from literature and visual references related to wayang. The results show that the redesigned Pandawa Lima characters successfully combine Javanese cultural values with a modern visual style that appeals to younger audiences. Validation by cultural experts ensured accuracy in relation to wayang conventions, while audience feedback reinforced the visual relevance within the digital media context. The implementation of the designs into 2D in-game assets demonstrates that integrating local culture through game media can serve as an effective strategy for preserving and reintroducing wayang values in the digital era. Keywords: Character design, Wayang, Digital game, Cultural preservation, Pandawa Lima